2018
DOI: 10.4103/ijem.ijem_285_17
|View full text |Cite|
|
Sign up to set email alerts
|

Diabetes management and the buddhist philosophy: Toward holistic care

Abstract: Buddhist philosophy is a way of life that transcends the borders of religion and focuses on the alleviation of suffering. The core teaching of Buddha was the Four Noble Truths: there is suffering, suffering is caused by clinging and ignorance, there is a way out of suffering and that way is the Noble Eightfold Path. The medical analogy in diabetes care would include identification of diabetes, understanding its etiopathogenesis, and how prognosis can be improved with appropriate care and management of this chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
1
3
0
1
Order By: Relevance
“…The results showed that the most influencing control of the health behavior-changing program is systolic blood pressure and follows by risk score, fasting blood sugar (FBS), smoking score, and body mass index (BMI). This result was similar to the previous study which reported that the health promotion program can reduce blood sugar and body mass index [4]. However, the most reduction of this program is the systolic blood pressure, consequently, this program is appropriate to apply for reducing the risk of Hypertension among Thai monks.…”
Section: Discussionsupporting
confidence: 90%
“…The results showed that the most influencing control of the health behavior-changing program is systolic blood pressure and follows by risk score, fasting blood sugar (FBS), smoking score, and body mass index (BMI). This result was similar to the previous study which reported that the health promotion program can reduce blood sugar and body mass index [4]. However, the most reduction of this program is the systolic blood pressure, consequently, this program is appropriate to apply for reducing the risk of Hypertension among Thai monks.…”
Section: Discussionsupporting
confidence: 90%
“…The first code of ethics from the five precepts within Buddhism doctrine is the abstinence from killing living beings, including intentionally ending one's own life by one's own hand, which is strictly prohibited by Buddhism (30,50). In the Buddhism teaching, suicidal behaviors are regarded as an "unskilled action", which would cause "dukkha" (unsatisfactoriness or suffering) to persons after the self-destructive behaviors (51).…”
Section: Discussionmentioning
confidence: 99%
“…Penyakit Diabetes Mellitus adalah penyakit metabolik kronis bersifat menahun dan ditandai oleh tingginya kadar glukosa didalam darah (Arif, 2018;Chang, Peng, Chang, & Chen, 2013). Analogi perawatan penyakit diabetes mellitus akan mencakup identifikasi diabetes, memahami etiopatogenesisnya, dan bagaimana prognosis dapat ditingkatkan dengan perawatan yang tepat dan pengelolaan gangguan kronis ini (Kalra et al, 2018).…”
Section: Pendahuluanunclassified